PENGARUH UKURAN PERUSAHAAN, UKURAN KANTOR AKUNTAN PUBLIK (KAP) DAN OPINI AUDITOR TERHADAP AUDIT DELAY - Sihite, Maria Veronica; Ramdani, Edon (LPPM Universitas Putera Batam, 2024)
This research aims to examine the influence of company size, KAP size, and auditor's opinion on audit delay in industrial companies listed on the Indonesia Stock Exchange with a research period of 2017-2022. This research uses a quantitative approach and uses associative methods. The type of data used in this research is secondary data. The data analysis method used in this research is Panel Data Regression Analysis using the Eviews version 10 application and Microsoft Excel. The data collection technique in this research is a purposive sampling technique with 55 populations becoming 23 company samples processed in this research. The research results show that simultaneously company size, KAP size, and auditor opinion have an effect on audit delay. Partially, company size and KAP size have no effect on audit delay, while the auditor's opinion has an effect on audit delay.